2021
DOI: 10.3389/fphar.2021.732887
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments About the Pathogenesis of Dry Eye Disease: Based on Immune Inflammatory Mechanisms

Abstract: Dry eye disease is a common and frequently occurring ophthalmology with complex and diverse causes, and its incidence is on the upward trend. The pathogenesis of DED is still completely clear. However, the immune response based on inflammation has been recognized as the core basis of this disease. In this review, we will systematically review the previous research on the treatment of DED in immune inflammation, analyze the latest views and research hotspots, and provide reference for the prevention and treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…Computational and Mathematical Methods in Medicine DED. The proinflammatory factors associated with DED that have been identified in the study are TNFα and IL-1, and CXCL8 is highly expressed in the eyes of patients with chronic dry syndrome [37,38]. MAPK is an important inflammatory target.…”
Section: Discussionmentioning
confidence: 89%
“…Computational and Mathematical Methods in Medicine DED. The proinflammatory factors associated with DED that have been identified in the study are TNFα and IL-1, and CXCL8 is highly expressed in the eyes of patients with chronic dry syndrome [37,38]. MAPK is an important inflammatory target.…”
Section: Discussionmentioning
confidence: 89%
“…Some of these improvements can be explained through the direct or indirect effect of HA on the osmolarity of the tear film, which in turn will reduce the osmotic stress at the ocular surface (Yu et al. 2021 ). Osmotic stress results from hyperosmolarity of the tear film and is one of the main mechanisms behind the vicious circle of DED, leading to inflammation and ocular surface damage (Bron et al.…”
Section: Discussionmentioning
confidence: 99%
“…Across the reviewed literature it is shown that DED treatment with HA improves tear film stability, evaporation, osmolarity, inflammation, ocular surface damage, as well as goblet-cell, epithelial, and meibomian gland health (Tables 1 and 2). Some of these improvements can be explained through the direct or indirect effect of HA on the osmolarity of the tear film, which in turn will reduce the osmotic stress at the ocular surface (Yu et al 2021). Osmotic stress results from hyperosmolarity of the tear film and is one of the main mechanisms behind the vicious circle of DED, leading to inflammation and ocular surface damage (Bron et al 2017).…”
Section: Pathophysiology Of Ded and Ha Drop Formulationmentioning
confidence: 99%
“…A key function of the innate immune system is to provide a physical barrier between the eye and the external environment, and thus to prevent the microbial attachment and toxins from crossing the surface epithelium. Components responsible for this function include mucins in the tear fluid, glycocalyx, corneal and conjunctival epithelium, and a series of anti-microbial defense proteins (lactoferrin, lysozyme, lipid transport proteins, tripeptides, defensins) ( 35 ).…”
Section: Immunomodulation Of Dry Eye Diseasementioning
confidence: 99%